Root causes analysis and countermeasures on unexpected perforation of tee pipe in the steam system of specialty chemical plant. (October 2019) - Fei, Jing-Lu; Yang, Xiao-Lei; Wang, Sheng-Hui; Gong, Yi; Yang, Zhen-Guo
Abstract: The tee pipe is generally considered as one of the vulnerable fittings in the entire piping owing to the sudden change of the flow direction. Hence, it is necessary to carry out failure analysis and reliability evaluation on the tee pipe for safe operation of the industrial piping. In this study, unexpected perforation as well as corrosion of tee pipe in the steam system of a large specialty chemical plant was addressed. Based on the systematic and comprehensive investigation including materials inspection, morphologies observation, scales detection, water quality inspection and finite element analysis, it was determined that the failure was primarily ascribed to the synergism between the localized corrosion and the flow erosion. Particularly, the vortex effect in the corrosion pit further aggravated the extent. The detailed mechanisms were discussed and the pertinent countermeasures were proposed. Achievement of this paper will help to better understand the synergistic effect of erosion and corrosion on the tee pipe under similar service conditions. Highlights: An unexpected perforation of tee pipe in the steam system of specialty chemical plant was investigated. The synergism between the localized corrosion and flow erosion in the tee pipe was addressed in detailed in this study. The vortex flows would aggravate the flow erosion extent, and eventually led to the large corrosion pit in this paper.